Wetlands of the Nile Basin: distribution, functions and contribution to livelihoods. - Rebelo, Lisa-Maria; McCartney, Matthew P. (Routledge, 2012)
Wetlands occur extensively across the Nile Basin and support the livelihoods ofmillions of people. Despite their importance, there are big gaps in the knowledge about the current status of these ecosystems, and how populations in the Nile use them. A better understanding is needed on the ecosystem services provided by the difl:erent types of wetlands in the Nile, and how these contribute to local livelihoods. While many ofthe Nile's wetlands arc inextricably linked to agricultural production systems the basis for making decisions on the extent to which, and how, wetlands can be sustainably used for agriculture is weak. Due to these infi)fl11atio!1 gaps, the future contribution of wetlands to agriculture is poorly understood, and wetlands are otten overlooked in the Nile Basin discourse on water and agriculture. While there is great potential for the further development of agriculture and fisheries, in particular in the wetlands of Sudan and Ethiopia, at the same time many wetlands in the basin are threatened by poor management practices and populations. In order to ensure that the future use of wetlands for agriculture will result in net benefits a much more strategic approach to wetland utilization is required; wetland management needs to be incorporated into basin management and, in addition, governance of wetlands should include a means of involving stakeholders from impacted or potentially impacted regions.